Seismic Loads - Fanella, David A. (McGraw-Hill's AccessEngineering., 2021)
This Excel workbook determines seismic loads in both Imperial and metric units in accordance with the 2018 IBC and ASCE/SEI 7-16. Included are the following: (1) determination of seismic ground motions, (2) determination of Seismic Design Category, (3) determination of seismic forces, design spectrum, drifts, and P-delta effects in accordance with the Equivalent Lateral Force Procedure, (4) determination of seismic forces on diaphragms, and (5) determination of seismic forces using the simplified method in ASCE/SEI 7-16.